Heterogeneity in 10-year course trajectories of moderate to severe major depressive disorder among veterans - V. Panaite; S. L. Luther; D. K. Finch; N. J. Cohen; S. K. Schultz; A. Tsalatsanis; P. N. Pfeiffer (Epidemiology and Psychiatric Sciences)
Abstract Aims Epidemiological studies show that despite the episodic nature, the long-term trajectory of depression can be variable. This study evaluated the heterogeneity of 10-year trajectory of major depressive disorder (MDD) related service utilization and associated clinical characteristics among US Veterans with a first diagnosis after 9/11.